Effects of a lateral inspiration training programme on butterfly stroke parameters - Barbosa, Tiago M. (2019)
Eleven university students, 9 males and 2 females, volunteered to participate in this study (mean age 20.0±1.0 years, 175.1±7.9cm of height and 71.278±10.569Kg of weight). These subjects followed 9 sessions of 100 minutes each, with the objective of learning and exercising the lateral inspiration on Butterfly stroke. Neither of them had ever made lateral inspiration on Butterfly. The evaluation occurred in at two points in time: one before (pre-test) and another after (post-test) the application of the training program. At each point in time, all subjects made two courses of 20 meters Butterfly, one using lateral inspiration and another adopting frontal inspiration, with a start in the water. Between the 5th meter and the 19th meter (i.e. within 14 meters) an observer recorded the time spent and the number of stroke cycles made. Therefore, the mean velocity displacement (V = 14.time– 1), the mean stroke frequency (SF = cycles.time–1) and the mean stroke length (SL = 14.cycles–1) according to Pelayo et al. (1997) procedures were analysed, as well as the stroke index (SI = V.SL) as it was proposed by Costill et al. (1985) and Tourny (1992). To determine the significance of the mean differences for each stroking parameter, ANOVA with repeated measures (p£0.05) was used.